2012
DOI: 10.3390/min2040435
|View full text |Cite
|
Sign up to set email alerts
|

Water- and Boron-Rich Melt Inclusions in Quartz from the Malkhan Pegmatite, Transbaikalia, Russia

Abstract: Abstract:In this paper we show that the pegmatite-forming processes responsible for the formation of the Malkhan pegmatites started at magmatic temperatures around 720 °C. The primary melts or supercritical fluids were very water-and boron-rich (maximum values of about 10% (g/g) B 2 O 3 ) and over the temperature interval from 720 to 600 °C formed a pseudobinary solvus, indicated by the coexistence of two types of primary melt inclusions (type-A and type-B) representing a pair of conjugate melts. Due to the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 31 publications
4
17
1
Order By: Relevance
“…This resonates with the suggestion of another group of researchers that a vitreous phase in a rehomogenised type-B melt inclusion from elsewhere is a gel rather than a glass, because a mica crystal grew within it over a week spent at room temperature [21]. However, the latter group classified quartz-hosted inclusions from the Malkhan pegmatites that are akin to the aforementioned ones as peralkaline to peraluminous type-A melt inclusions (those in Figure 3a-c) [62]. These authors also reported quartz-hosted peralkaline type-B and type-C melt inclusions from the same locality, which consist of a large sassolite crystal, sometimes a few small silicate crystals, and a fluid with a vapour bubble (Figure 3d,e) [62].…”
Section: Evidence From Inclusions In Mineralssupporting
confidence: 79%
“…This resonates with the suggestion of another group of researchers that a vitreous phase in a rehomogenised type-B melt inclusion from elsewhere is a gel rather than a glass, because a mica crystal grew within it over a week spent at room temperature [21]. However, the latter group classified quartz-hosted inclusions from the Malkhan pegmatites that are akin to the aforementioned ones as peralkaline to peraluminous type-A melt inclusions (those in Figure 3a-c) [62]. These authors also reported quartz-hosted peralkaline type-B and type-C melt inclusions from the same locality, which consist of a large sassolite crystal, sometimes a few small silicate crystals, and a fluid with a vapour bubble (Figure 3d,e) [62].…”
Section: Evidence From Inclusions In Mineralssupporting
confidence: 79%
“…Figure 4d displays the extreme Cs enrichment near the solvus crest of the Melt-H 2 O -B 2 O 3 system as Cs-pentaborate (Ramanite-(Cs). At first, this Cs-pentaborate was found in pegmatite material from the Isle of Elba (see [21] -later also in Malkhan (Thomas et al, 2012) [22] and Ehrenfriedersdorf (Sauberg mine). The Lorentzian distribution of Cs vs. B is untypical, and Cs vs. H 2 O is typical for some elements (Be, Sn, and others [5,6].…”
Section: Resultsmentioning
confidence: 98%
“…However, the concentrations of B and Ti (Table 2) were much higher than typical for quartz deposits of different origins [19]. The major, minor, and trace element contents, respectively, suggested that the powder quartz mine was associated with geological environment and mineralization of felsic rocks of pegmatitic origin as indicated by the higher B and Ti contents [20].…”
Section: Chemical Composition Analysismentioning
confidence: 89%